Penggunaan Karbon Aktif Dari Limbah Pertanian Untuk Penyisihan Logam Fe Pada Air Sumur Bor - Lidya Astuti; Lita Darmayanti; Elvi Yenie (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Water is a very vital need for living things. Clean water must meet physical and chemical quality requirements. The problem that is often encountered is the quality of ground water used does not meet the requirements as clean water. Deep and shallow groundwater contains a lot of high iron (Fe). Therefore, this article will present a brief review of the utilization of corncorb waste as an adsorbent for reducing Fe metal in groundwater.Keywords : Adsorption, metal Fe, corncob